Cover Image, Volume 50, Issue 6. Issue 6 (10th December 2019) - Priyashantha, Hasitha; Lundh, Åse; Höjer, Annika; Hetta, Mårten; Johansson, Monika; Langton, Maud
Abstract : The cover image is based on the Original Article Interactive effects of casein micelle size and calcium and citrate content on rennet‐induced coagulation in bovine milk by Hasitha Priyashantha et al., https://doi.org/10.1111/jtxs.12454 .